2017
DOI: 10.1080/03080188.2017.1380468
|View full text |Cite
|
Sign up to set email alerts
|

Investigating consciousness in the sleep laboratory – an interdisciplinary perspective on lucid dreaming

Abstract: Article 25fa pilot End User AgreementThis publication is distributed under the terms of Article 25fa of the Dutch Copyright Act (Auteurswet) with explicit consent by the author. Dutch law entitles the maker of a short scientific work funded either wholly or partially by Dutch public funds to make that work publicly available for no consideration following a reasonable period of time after the work was first published, provided that clear reference is made to the source of the first publication of the work.This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…I just remember the last one was '8 minus 6.''' (For further details on sleep monitoring and terminology, see Nir and Tononi, 1 Appel et al, 6 and Baird et al 7 ) nap, near the beginning of a period of REM sleep. He indicated that he was in a lucid dream with a series of three left-right eye movements (termed LRLRLR).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…I just remember the last one was '8 minus 6.''' (For further details on sleep monitoring and terminology, see Nir and Tononi, 1 Appel et al, 6 and Baird et al 7 ) nap, near the beginning of a period of REM sleep. He indicated that he was in a lucid dream with a series of three left-right eye movements (termed LRLRLR).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a ''lucid dream'' differs in that the dreamer gains the elusive insight of being in a dream. 6,7 Lucid dreams occur predominantly during REM sleep and can be accompanied by eye-movement signals used to indicate that dreamers recognize that they are dreaming 8,9 or to transmit other information such as time-stamping dream events. 10,11 However, lucid dreaming is a notoriously rare phenomenon and lucid dreams can seldom be summoned at will, which has made it difficult for researchers to capture them in the lab in a reliable manner.…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed that the methodological quality of the works analyzed was relatively low, and none of the induction techniques reported in these studies induced LD reliably and consistently. More research is needed to increase our understanding of external sensory stimulus processing during sleep and the conditions and the stimulus properties required for reliable dream content incubation, while preventing awakenings (Appel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Entangled with the issue of measuring lucidity is the question of how to measure lucid dream induction success . The immense promise of lucid dreaming is limited by the capacity to experimentally induce lucidity (Appel et al, 2018), and thus a leading goal of the field is to develop reliable lucid dream induction methods. The method of quantifying induction success rate is often inconsistent across experiments, and might be one of the contributing factors to literature discrepancies (Stumbrys, Erlacher, Schädlich, et al, 2012).…”
Section: Methodological Decisions In Reporting Induction Successmentioning
confidence: 99%